Resistance of human immunodeficiency virus type 1 to integrase strand transfer inhibitors in Croatia : the first report - Planinić, Ana (Array, 2019)
Integrase strand transfer inhibitors (INSTIs) are the latest class of antiretroviral drugs that prevent the integration of proviral DNA into the host genome. The aim of this study was to describe, for the first time, INSTI resistance mutations observed in Croatian HIV-infected patients. Methods: The study was conducted between March 2016 and September 2018 and included 4 previously untreated patients (antiretroviral, ARV-naive) as well as 18 unsuccessfully treated HIV-infected patients (ARV-experienced) that have been tested for INSTI resistance. The genetic data on INSTI resistance was obtained by population-based sequencing of the integrase gene. Resistance analysis to other classes of antiretroviral drugs has been performed in some patients by sequencing the protease gene and a part of the reverse transcriptase HIV-1 gene. Results: INSTI resistance mutations were not found in ARV-naive patients. Mutations associated with resistance to INSTIs have been observed in 5 of 18 (27.8%) patients failing INSTI-based ARV regiment. Resistance to INSTIs in ARV-experienced patients was attributed to major resistance mutations Q148R, N155H and E92Q that confer resistance to two INSTIs (raltegravir and elvitegravir). Conclusions: The results of this study describe the first 5 cases of ARV-experienced HIV-1 infected patients with clinically significant resistance to INSTIs, and emphasize the need for continuous surveillance of INSTI resistance in patients experiencing virological failure to antiretroviral treatment in Croatia.